Beternak Sapi Secara Tradisional - Jumarni Jumarni; Raemon Raemon (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The purpose of this study was to find out and describe the traditional cattle farming system and the cattle profit-sharing system in Amoito Siama Village. The research method used in this research is descriptive qualitative. The results of this study indicate that the traditional cattle raising system in Amoito Siama Village begins with the preparation process for raising cattle, followed by the treatment process starting from feeding the cattle, giving the cattle water, and preparing the stables for the cattle. Furthermore, the profit-sharing system between the cow owner and the cattle keeper starts with building a relationship between the cow owner and the cow keeper to then enter into a profit-sharing agreement in which they agree with each other. There are two methods for the profit-sharing system in Amoito Siama Village, namely by sharing livestock or by paying wages.